A Review of Risk Factors for Non-Communicable Diseases Among Bus Drivers - Arun R; Meriton Stanly A (Medsci Publications, 2022)
A significant threat among the developing countries towards health and development in the current era is attributed by non-communicable diseases. These diseases contribute to major portion of morbidity and mortality globally. It has been predicted that with such an alarming rise in these cases, NCDs will exceed communicable, maternal, perinatal, and nutritional disease as the common causes of death by 2030. Without any action towards this menace the burden of these diseases will continue to escalate overwhelming our capacity to address them. Metropolitan drivers are a group of people who spend their majority of time in a polluted, noisy and a dangerous workplace. With the very few data on the predisposing risk factors among this population, this review help us identifying such factors among the drivers which can help in formulating new policies and improve their health.